Peran TPA Daarul Qur’an dalam Meningkatkan Bacaan Al-Qur’an dan Pembinaan Akhlak Anak di Air Bangis Pasaman Barat - Intan Maharani; Misra Misra (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to explore the role of the Daarul Qur'an Al-Qur'an Education Park (TPA) in improving Al-Qur'an reading and developing children's morals in Air Bangis, West Pasaman. The method used is a qualitative approach with interview techniques, observation and documentation. The research subjects consisted of TPA managers, teachers, and children who took part in learning programs at the TPA. The research results show that TPA Daarul Qur'an has made a significant contribution to improving children's Al-Qur'an reading abilities, which is reflected in the development of more fluent and correct reading abilities. Apart from that, TPA also plays an active role in moral development, through teaching the moral values ​​contained in the Koran and the example set by its teachers. This moral development has a positive impact on children's attitudes and behavior, both at home and at school. Overall, this research concludes that TPA Daarul Qur'an makes a very important contribution to the spiritual and moral development of children in Air Bangis, West Pasaman.